Investigation of Fe2O3/SiO2 Nanocomposite by FESEM and TEM. (31st March 2013) - Ang, B. C.; Yaacob, I. I.; Nurdin, Irwan
Abstract : Superparamagnetic maghemite nanoparticles were synthesized using Massart's procedure. Nanocomposites that consist of the synthesized maghemite nanoparticles and silica were produced by dispersing the as-synthesized maghemite nanoparticles into the silica xerogel prepared by sol-gel technique. The system was then heated for 3 days at 140°C. The structure, morphology, and texture of the system were analysed by FESEM and TEM. The result from FESEM showed that the silica gel forms a network structure, which contained numerous pores, with an average pore size of 15 nm. EDX line profile analysis was carried out, and the result indicated that the embedded particles were iron oxide. EELS showed the presence of Fe-L2 signal, which confirmed the presence of iron oxide particles within the silica matrix. The average diameters were 5.0 nm for as-synthesized maghemite nanoparticles and 4.4 nm for the embedded maghemite nanoparticles in silica xerogel matrix. The embedded maghemite nanoparticles in nanocomposite also showed a narrower distribution compared to as-synthesized particles. The magnetization values at 10 kOe applied field, Ms 10 kOe, were 9.53 emu/g and 1.79 emu/g for as-synthesized and embedded nanoparticles, respectively. A reduction in average crystallite size was observed for the dispersed maghemite particles after formation of the nanocomposite indicating a slight dissolution of maghemite nanoparticles in silica gel.